Enhanced Non-traditional Learning Environment for Communication Engineers Using Free OpenSource Software Tools - Maragatharaj, S.; Rathinakumar, K.; Kumar, M. Dinesh (2013 IEEE Fifth International Conference on Technology for Education (t4e 2013), 2013)
Engineering is basically the application of the laws of nature for the benefit of the human kind. In the curriculum of majority of engineering branches there are certain abstract concepts. The students find it difficult to understand these concepts. There are many methods which are being followed to make the students under stand concepts. One such method is the use of CAD tools When computers came into class rooms, the need for CAD tools also arose [1]. They help the students to visualize many basic concepts which, they otherwise cannot see in the physical world. In this 21 st century , dominated by social networking, the tools required to educate them have also come to be available in free of cost. Such tools are called open source software or FOSS tools. We have proposed a teaching methodology that involves the usage of open source software tools along with traditional teaching which enable the communication engineering students to understand complex concepts pertaining to the subject of Antenna and wave propagation. We carried out an experiment with forty students from fifth semester Electronics and Communication Engineering department. The students used a FOSS tool and gave a test based on designing of various antennas with desired radiation patterns by selecting different parameters before and after using the tool. The scores of the two tests show that there was an increase in the marks obtained by students in the test after using the tool. Thus the use of FOSS tool helped students perform better in the test. This may be because the tool has visualizations which help student understand the abstract concepts such as antenna radiation pattern and wave propagation.